Social media and sports - Clavio, Galen (Champaign, Illinois Human Kinetics, 2021)
Social media communications play a huge role in the day-to-day operations of sports teams and organizations. Both current and aspiring sport business professionals need to know how to best leverage social media to meet their organizational goals, and Social Media and Sports will help pave the way by emphasizing the strategic, creative, and logistical elements of effective social media practices. This text examines the impact of social media on sports and the categories of content used. It provides a better understanding of the social media environment by discussing audiences and networks and evaluating how online communities act and interact. The final chapters assemble the building blocks into practical application, covering brand management strategies and overall social media presence from the perspective of a member of the sports media, a representative of a team or league, or an individual athlete. A related web resource online learning aids delivered via HKPropel offers a detailed look into major social networks and their technological elements, plus best practices, tips, and tricks for utilizing a variety of social media platforms. Social Media and Sports offers a practical approach to understanding social media communications in the sports industry, with usefulness that applies to myriad sport-related careers where knowledge of effective social media usage will maximize career potential. The web resource and an instructor guide are is available online for adopting instructors.
Keywords: Communication in sports; Social media in sports